Avoiding Trouble: Exploring Environmental Risk Information Avoidance Intentions. Issue 2 (February 2020) - Kahlor, Lee Ann; Olson, Hilary Clement; Markman, Arthur B.; Wang, Wan
This study explores predictors of risk information avoidance intentions in the context of a novel environmental threat—induced earthquakes in Texas. Given the paucity of research on risk information avoidance, this work was guided by a cognitive information behavior model. Survey data ( N = 541) from a random sample of Texas adults allowed us to explore these variables. While previous research has shown risk information seeking intentions to be robustly guided by a number of constructs, our current data suggest that risk information avoidance intentions may be more narrowly predicated on risk information avoidance-related subjective norms, attitudes, and perceived knowledge insufficiency. We discuss these findings and suggest avenues for future environmental risk research.